2021
DOI: 10.1177/1359105321990793
|View full text |Cite
|
Sign up to set email alerts
|

Men’s attitudes toward mask-wearing during COVID-19: Understanding the complexities of mask-ulinity

Abstract: Path analyses indicated that the relationship between conformity to masculine norms (CMN) and attitudes toward mask-wearing to protect from COVID-19 was mediated by perceived benefits, perceived barriers, confidence in the scientific community, and empathy toward vulnerable persons, and that political ideology moderated the indirect effects from CMN to men’s attitudes. Efforts to improve men’s participation in combatting COVID-19 should address the perceptions and attitudes related to conforming to traditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
53
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 67 publications
(58 reference statements)
6
53
0
2
Order By: Relevance
“…Male gender and younger age have been identified as predictors of not wearing face masks in publics places. 6,7,8,9 That attitude has been attributed to inflated self-perception of invulnerability and COVID-19 denialism. 7 It is also influenced by perceptions of overall compliance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Male gender and younger age have been identified as predictors of not wearing face masks in publics places. 6,7,8,9 That attitude has been attributed to inflated self-perception of invulnerability and COVID-19 denialism. 7 It is also influenced by perceptions of overall compliance.…”
mentioning
confidence: 99%
“…6,7,8,9 That attitude has been attributed to inflated self-perception of invulnerability and COVID-19 denialism. 7 It is also influenced by perceptions of overall compliance. Barile et al 8 found that intention to wear face masks increased when subjects perceived that "some" or "most" others were wearing.…”
mentioning
confidence: 99%
“…Though, behavioural explanations arising from gendered socialisation and norms have also been offered for why men are more likely to catch, develop symptoms and die from Covid-19 (Ruxton & Burrell, 2020, p. 14). An article in The New York Times, for instance, argued in 2020 that adherence to 'toxic masculinity' is a predictor of whether or not men are likely to wear masks (Gupta, 2020), something which has empirical support (Mahalik, Bianca, & Harris, 2021), whilst others have shown that men are far less likely to comply with recommendations and more likely to under-rate the threat of Covid-19 than women (Galasso et al, 2020). Men also represent a lower percentage of those who are vaccinated with even one dose of a vaccine in many countries.…”
Section: Thinking About Risk and Vulnerability In Csmmmentioning
confidence: 99%
“…Nevertheless, it is important to note that there is a growing body of evidence suggesting that certain masculine traits or norms can act as protective factors for men's wellbeing or are unrelated to mental health (Gerdes & Levant, 2018;Lin et al, 2021;Van Doorn et al, 2021), while the rigid adherence to traditional masculinity is in general linked to worse mental health and health behaviors (Lippa et al, 2000;Mahalik et al, 2021;Wong et al, 2017). However, traditional masculinity ideology has never been investigated as potential moderator of the association between experienced loss of social status and suicide risk in men.…”
Section: Introductionmentioning
confidence: 99%